Multiplex SARS-CoV-2 Genotyping Reverse Transcriptase PCR for Population-Level Variant Screening and Epidemiologic Surveillance - Wang, Hannah; Miller, Jacob A.; Verghese, Michelle; Sibai, Mamdouh; Solis, Daniel; Mfuh, Kenji O.; Jiang, Becky; Iwai, Naomi; Mar, Marilyn; Huang, ChunHong; Yamamoto, Fumiko; Sahoo, Malaya K.; et al. (Journal of clinical microbiology, 2021)
The emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants with concerning phenotypic mutations is of public health interest. Genomic surveillance is an important tool for a pandemic response, but many laboratories do not have the resources to support population-level sequencing. The emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants with concerning phenotypic mutations is of public health interest. Genomic surveillance is an important tool for a pandemic response, but many laboratories do not have the resources to support population-level sequencing. We hypothesized that a nucleic acid amplification test (NAAT) to genotype mutations in the viral spike protein could facilitate high-throughput variant surveillance. We designed and analytically validated a one-step multiplex allele-specific reverse transcriptase PCR (RT-qPCR) to detect three nonsynonymous spike protein mutations (L452R, E484K, N501Y). Assay specificity was validated with next-generation whole-genome sequencing. We then screened a large cohort of SARS-CoV-2-positive specimens from our San Francisco Bay Area population. Between 1 December 2020 and 1 March 2021, we screened 4,049 unique infections by genotyping RT-qPCR, with an assay failure rate of 2.8%. We detected 1,567 L452R mutations (38.7%), 34 N501Y mutations (0.84%), 22 E484K mutations (0.54%), and 3 (0.07%) E484K plus N501Y mutations. The assay had perfect (100%) concordance with whole-genome sequencing of a validation subset of 229 specimens and detected B.1.1.7, B.1.351, B.1.427, B.1.429, B.1.526, and P.2 variants, among others. The assay revealed the rapid emergence of the L452R variant in our population, with a prevalence of 24.8% in December 2020 that increased to 62.5% in March 2021. We developed and clinically implemented a genotyping RT-qPCR to conduct high-throughput SARS-CoV-2 variant screening. This approach can be adapted for emerging mutations and immediately implemented in laboratories already performing NAAT worldwide using existing equipment, personnel, and extracted nucleic acid.